KISAH KELUARGA TELADAN DALAM AL QURAN (INSPIRASI MEMBANGUN NEGARA YANG THAYYIBAH) - Sholihin, Rahmat (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
This article aims to discuss some exemplary family stories in the Koranthat could be an inspiration to build a strong nation. This is because a greatstrong nation contains of individuals who grew up in families. Family, thus,became the first school (madrasah ula) for an individual. There are at leastsix families who become the focus of this paper; the family of Imran,Ibrahim as., Luqman, Ya'qub as, Daud as, and Syuaib as. These Familiescan become inspirations in realizing the solid state and civil society